Estrogen-induced inhibition of spermatogenesis in zebrafish is largely reversed by androgen - Assis, Luiz Henrique de Castro; Nobrega, Rafael Henrique de [UNESP]; Esther Gomez-Gonzalez, Nuria; Bogerd, Jan; Schulz, Rudiger Winfried (Bioscientifica Ltd, 2018)
The hormonal regulation of spermatogenesis involves both gonadotropins and steroid hormones. Long-term in vivo exposure of adult zebrafish to estrogen impaired spermatogenesis associated with an androgen insufficiency, possibly induced by inhibiting gonadotropin release. Using this experimental model, we investigated if androgen treatment could enhance spermatogenesis, while maintaining the inhibition of gonadotropin release through continued estrogen exposure. Moreover, we also exposed animals to androgen alone, in order to examine androgen effects in the absence of estrogen-induced gonadotropin inhibition. Estrogen exposure depleted type B spermatogonia, meiotic and postmeiotic germ cells from the adult testis, but promoted the proliferation of type A undifferentiated spermatogonia, which accumulated in the testis. This change in germ cell composition was accompanied by reduced mRNA levels of those growth factors (e.g. insl3 and igf3) expressed by testicular somatic cells and known to stimulate spermatogonial differentiation in zebrafish. Additional androgen (11-ketoandrostenedione, which is converted to 11-ketotestosterone) treatment in vivo reversed most of the effects of estrogen exposure on spermatogenesis while insl3 and igf3 transcript levels remained suppressed. When androgen treatment was given alone, it promoted the production of haploid cells at the expense of spermatogonia, and increased transcript levels of some growth factor and hormone receptor genes, but not those of insl3 or igf3. We conclude that estrogen exposure efficiently inhibits spermatogenesis because it induces androgen insufficiency and suppresses gonadotropin-regulated growth factors known to stimulate germ cell differentiation. Moreover, our results suggest that androgens and the growth factors Insl3 and Igf3 stimulate spermatogenesis via independent pathways.
Keywords: spermatogenesis; estrogen; gonadotropins; androgen insufficiency; zebrafish